A rapid diagnostic tool for two species of Tetradacus (Diptera: Tephritidae: Bactrocera) based on species‐specific PCR. (24th February 2013) - Jiang, F.; Li, Z. H.; Wu, J. J.; Wang, F. X.; Xiong, H. L.
Abstract Bactrocera minax and Bactrocera tsuneonis are two sibling species of the Bactrocera subgenus Tetradacus with significant quarantine importance in Asia. It is difficult to identify or distinguish them only based on morphological characteristics. In this study, microscopic observations showed that morphological features of adult samples were congruent with the diagnosis of the two species. In this study, we describe species‐specific PCR for the molecular identification of B. minax and B. tsuneonis. Species‐specific primer pairs were designed on the basis of variations in the mtDNA COI barcode sequences among Bactrocera spp.. A 499 bp‐specific fragment of B. minax and a 337 bp absolute product of B. tsuneonis were generated by their respective primer pairs, whilst no such diagnostic bands were present in any of the other fruit fly species tested. The results of the sensitivity test demonstrated that the detection limit of DNA template concentration was 1 ng/μl for B. minax and 0.1 ng/μl for B. tsuneonis. This assay exhibited high specificity, reliability, rapid and low cost for all ontogenetic stages. Our data show that species‐specific PCR is a powerful tool that can be used for the identification of B. minax and B. tsuneonis in quarantine work.